2021
DOI: 10.1038/s41598-021-97496-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of individual variation in timing to delay-discounting

Abstract: Delay-discounting studies in neuroscience, psychology, and economics have been mostly focused on concepts of self-control, reward evaluation, and discounting. Another important relationship to consider is the link between intertemporal choice and time perception. We presented 50 college students with timing tasks on the range of seconds to minutes and intertemporal-choice tasks on both the time-scale of seconds and of days. We hypothesized that individual differences in time perception would influence decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…delay perceptions. This is in line with studies indicating that time perception plays a significant role in delay discounting [ (103)(104)(105)(106)(107); see also (108)]. This scaling parameter s, as well as the discount parameter κ, moreover differed significantly between the reward and the loss condition.…”
Section: Discussionsupporting
confidence: 90%
“…delay perceptions. This is in line with studies indicating that time perception plays a significant role in delay discounting [ (103)(104)(105)(106)(107); see also (108)]. This scaling parameter s, as well as the discount parameter κ, moreover differed significantly between the reward and the loss condition.…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed that in the general population discount factors across time-horizons were highly related as in the students population in our studies before (Lukinova et al, 2019; Lukinova and Erlich, 2021). In this paper, however, we improved our modeling.…”
Section: Discussionsupporting
confidence: 90%
“…We find that time preferences are stable across time-horizons: between days and seconds, r = 0.46 and between days and weeks, r = 0.96 (Figure 2A-D). Therefore, we are able to replicate our previous results (Lukinova et al, 2019; Lukinova and Erlich, 2021) in a nonstudent population. We also report the between tasks and between sessions Pearson correlations of subjects’ discount factors (log( k )) in Table 1 for all models under consideration.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…An important but unaddressed issue is the cognitive components underlying delay discounting. Delay discounting consists of a variety of cognitive components, such as reward valuation, time perception, conflict detection, and cognitive control ( Wittmann and Paulus, 2008 ; Claus et al, 2011 ; Frost and McNaughton, 2017 ; Dennis et al, 2020 ; Lukinova and Erlich, 2021 ). However, the behavioral index of the delay discounting used in our study ( k value) was not able to be further decomposed into these cognitive components.…”
Section: Discussionmentioning
confidence: 99%